2020
DOI: 10.3390/cancers12051176
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Unresectable Stage IIIC and IV Melanoma in the Era of New Systemic Therapy

Abstract: Opportunities for surgical treatment in metastatic melanoma patients have re-emerged due to the development of novel systemic therapeutics over the past decade. The aim of this study is to present data on outcomes of surgery in patients with unresectable stage IIIC and IV melanoma, who have previously been treated with immunotherapy or targeted therapy. Data was extracted from the Dutch Melanoma Treatment Registry (DMTR) on 154 patients obtaining disease control to systemic therapy and undergoing subsequent su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This finding holds when the disease progression pattern during ICI treatment regards a few sites, which can be surgically approached or tackled with radiotherapy, resulting in one interpretation of the correlative analysis. Previous studies reported favorable survival when distant melanoma tissues were removed via surgery after checkpoint blockade, especially when they responded to ICI treatment ( 22 , 23 ). Administration of chemotherapy was highly observed in patients in the non-ICI era, mostly because it was the only treatment modality available.…”
Section: Discussionmentioning
confidence: 99%
“…This finding holds when the disease progression pattern during ICI treatment regards a few sites, which can be surgically approached or tackled with radiotherapy, resulting in one interpretation of the correlative analysis. Previous studies reported favorable survival when distant melanoma tissues were removed via surgery after checkpoint blockade, especially when they responded to ICI treatment ( 22 , 23 ). Administration of chemotherapy was highly observed in patients in the non-ICI era, mostly because it was the only treatment modality available.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant immunotherapies that have been used in melanoma clinical trials are: Interferon-α-2b (IFN-α-2b), Interleukin (IL)-2, melanoma cell vaccines, BCG (Bacillus Calmette-Guérin), and immune checkpoint inhibitors (ICI) immunotherapy in post-surgical, disease-free AJCC (American Joint Committee on Cancer) stage III and IV patients [ 1 , 2 , 3 , 4 ]. Newer immunotherapies using monoclonal antibodies, such as ICIs, which target against CTLA-4, PD-1, or PD-L1 [ 5 , 6 , 7 ], have improved overall survival time when used as both adjuvant and neo-adjuvant therapies in AJCC stage III/IV melanoma patients [ 8 , 9 , 10 , 11 ]. ICI agents, nivolumab and pembrolizumab therapies, which are less toxic and have better recurrence-free survival rates, are the most effective and current standard of care for the treatment of melanoma patients [ 1 ].…”
Section: Introductionmentioning
confidence: 99%